Communicable Diseases Intelligence volume 13 issue 16 - 14 August 1989 - whole issue - No author listed (Communicable Diseases Intelligence, 1989)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme Original article Salmonella typhimurium phage type 201a in South Australia Isolation of Legionella from cooling towers supplied by artesian bores A case of subacute sclerosing panencephalitis (SSPE) [also known as Dawson disease] in a previously immunised child An outbreak of Varicella amongst nursing staff Australia - Communicable Diseases Intelligence Period 20/07/1989 to 02/08/1989 Notifiable diseases reported in Australia: 1988 1 January to 31 December 1988